Necrosis Avidity of Organic Compounds: A Natural Phenomenon with Exploitable Theragnostic Potentials - Miranda Cona, Marlein; Oyen, Raymond; Ni, Yicheng (Current Medicinal Chemistry, 2015)
Necrosis is an in vivo chaotic event distinguished by uncontrolled disintegration of the cell membrane leading to cytolysis, inflammation and tissue destruction followed by a healing or regenerating process. Targeting necrosis may offer potential diagnostic, therapeutic and/or theragnostic applications in translational medicine. This article reviews the current concept of necrosis including definition, etiology and pathophysiology. The evolution and development of a wide diversity of necrosis targeting agents and their potential applications in preclinical and clinical settings are also elaborated and discussed.
Keywords: necrosis